Insights into pituitary tumorigenesis: from Sanger sequencing to next-generation sequencing and beyond. Issue 6 (2nd November 2019) - Shen, Angeline Jia Jia; King, James; Scott, Hamish; Colman, Peter; Yates, Christopher J
ABSTRACT: Introduction : This review explores insights provided by next-generation sequencing (NGS) of pituitary tumors and the clinical implications. Areas covered : Although syndromic forms account for just 5% of pituitary tumours, past Sanger sequencing studies pragmatically focused on them. These studies identified mutations in MEN1, CDKN1B, PRKAR1A, GNAS and SDHx causing Multiple Endocrine Neoplasia-1 (MEN1), MEN4, Carney Complex-1, McCune Albright Syndrome and 3P association syndromes, respectively. Furthermore, linkage analysis of single-nucleotide polymorphisms identified AIP mutations in 20% with familial isolated pituitary adenomas (FIPA). NGS has enabled further investigation of sporadic tumours. Thus, mutations of USP8 and CABLES1 were identified in corticotrophinomas, BRAF in papillary craniopharyngiomas and CTNNB1 in adamantinomatous craniopharyngiomas. NGS also revealed that pituitary tumours occur in the DICER1 syndrome, due to DICER1 mutations, and CDH23 mutations occur in FIPA. These discoveries revealed novel therapeutic targets and studies are underway of BRAF inhibitors for papillary craniopharyngiomas, and EGFR and USP8 inhibitors for corticotrophinomas. Expert opinion : It has become apparent that single-nucleotide variants and small insertion/deletion DNA mutations cannot explain all pituitary tumorigenesis. Integrated and improved analyses including whole-genome sequencing, copy number, and structural variation analyses, RNA sequencing and epigenomic analyses, with improved genomic technologies, are likely to further define the genomic landscape.